The Effectiveness of Student Worksheet to Improve Students Problem Solving Skills on the Material of Factors that Affect the Reaction Rate Based on Inquiry Learning - Apriliane, Riza; Suyono, Suyono; Delhita, Antina (Jurnal Pijar Mipa, 2025)
Problem-solving ability is one of the abilities that support the achievement of the Profil Pelajar Pancasila. In reality, problem-solving skills are still low and need to be improved. Based on the literature study, student worksheet learning tools using the inquiry model can train problem-solving skills. The research objective is expected to produce an effective student worksheet to improve problem-solving skills on the material of factors that affect the reaction rate. The student worksheet was developed following the ADDIE (Analyze, Design, Develop, Implement, Evaluate) stages, up to the develop and pilot implementation stage. The pilot implementation target was 28 students of class XI-3 SMA Negeri 7 Surabaya. Student worksheets in this study were developed referring to the indicators of problem-solving ability, namely recognising the problem, describing the problem, planning a solution, executing the plan, and evaluating the solution. The effectiveness of the student worksheets was determined based on the results of the problem-solving ability test. The effectiveness test design used was a one-group pretest-posttest Design. Pretest and posttest data were analyzed using a normality test and a paired t-test. The student worksheet developed was declared effective if there was an increase in students' problem-solving ability test scores between before and after the trial.  The problem-solving ability test results were tested with the Shapiro-Wilk test. The prerequisite test results showed normal distribution because the p-value> 0.05. Followed by hypothesis testing using a paired t-test (one-tail).  Data analysis using a paired t-test (one-tailed) resulted in a p-value of 0.000 <0.005, so there was a significant increase in the problem-solving score. Thus, student worksheets developed using the inquiry model are declared effective for improving students' problem-solving skills in the material of factors that affect the reaction rate.